Exogenous melatonin confers salt stress tolerance to Chlamydomonas reinhardtii (Volvocales, Chlorophyceae) by improving redox homeostasis. Issue 6 (1st November 2018) - Zhang, Yujing; Gao, Wenying; Lv, Yawei; Bai, Qingqing; Wang, Yingjuan
Abstract: Melatonin (MT; N-acetyl-5-methoxy-tryptamine), a natural derivative of tryptophan, is a central biomolecule synthesised by almost all organisms, including animals and plants. As an antioxidant, MT is involved in many cell responses associated with the protection of plants against abiotic stress. However, there are few studies on the function of MT in microalgae. Our work focused on the relationship between exogenous MT and salt stress in the single-celled eukaryote Chlamydomonas reinhardtii, evaluating for growth, cell morphology, malondialdehyde (MDA) content (the peroxidation product of the cell membrane), activity of antioxidant enzymes and MT concentration under 100 mM NaCl treatment. Growth of Chlamydomonas was promoted at MT concentrations of 0.1 and 1.0 μM, but at 10 and 100 μM, MT was associated with negative effects on growth. MT at 1 μM maintained intact cell morphology and cellular aggregation in an unfavourable salt environment. MT concentrations of 0.1, 1 and 10 μM MT led to increased activity of the antioxidants superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) but reduced MDA. In conclusion, by increasing relative enzyme activity and maintaining a balanced redox state, exogenous MT may improve salt tolerance of C. reinhardtii to allow normal growth. A suitable concentration of exogenous MT improved the growth of C. reinhardtii in a salt environment and increased the activity of antioxidant system–related enzymes to protect cells. These results provide insight into the function of MT in a model green alga.